Comparison of non-invasive to invasive oxygenation ratios for diagnosing acute respiratory distress syndrome following coronary artery bypass graft surgery: a prospective derivation-validation cohort study - Bashar, Farshid R.; Vahedian-Azimi, Amir; Farzanegan, Behrooz; Goharani, Reza; Shojaei, Seyedpouzhia; Hatamian, Sevak; Mosavinasab, Seyed M. M.; Khoshfetrat, Masoum; Khatir, Mohammad A. K.; Tomdio, Anna; Miller, Andrew C. (My University, 2018)
Objective: To determine if non-invasive oxygenation indices, namely peripheral capillary oxygen saturation (SpO2)/ fraction of inspired oxygen (Fi O2) and partial pressure of alveolar oxygen (PAO2)/Fi O2 may be used as effective surrogates for the partial pressure of arterial oxygen (PaO2)/Fi O2. Also, to determine the SpO2/Fi O2 and PAO2/Fi O2 values that correspond to PaO2/Fi O2 thresholds for identifying acute respiratory distress syndrome (ARDS) in patients following coronary artery bypass graft (CABG) surgery. Methods: A prospective derivation-validation cohort study in the Open-Heart ICU of an academic teaching hospital. Recorded variables included patient demographics, ventilator settings, chest radiograph results, and SPO2, PaO2, PAO2, SaO2, and Fi O2. Linear regression modeling was used to quantify the relationship between indices. Receiver operating characteristic (ROC) curves were used to determine the sensitivity and specificity of the threshold values. Results: One-hundred seventy-five patients were enrolled in the derivation cohort, and 358 in the validation cohort. The SPO2/Fi O2 and PAO2/Fi O2 ratios could be predicted well from PaO2/Fi O2, described by the linear regression models SPO2/Fi O2 = 71.149 + 0.8PF and PAO2/Fi O2 = 38.098 + 2.312PF, respectively. According to the linear regression equation, a PaO2/Fi O2 ratio of 300 equaled an SPO2/Fi O2 ratio of 311 (R2 0.857, F 1035.742, < 0.0001) and a PAO2/Fi O2 ratio of 732 (R2 0.576, F 234.887, < 0.0001). The SPO2/Fi O2 threshold of 311 had 90% sensitivity, 80% specificity, LR+ 4.50, LR- 0.13, PPV 98, and NPV 42.1 for the diagnosis of mild ARDS. The PAO2/Fi O2 threshold of 732 had 86% sensitivity, 90% specificity, LR+ 8.45, LR- 0.16, PPV 98.9, and NPV 36 for the diagnosis of mild ARDS. SPO2/ Fi O2 had excellent discrimination ability for mild ARDS (AUC ± SE = 0.92 ± 0.017; 95% CI 0.889 to 0.947) as did PAO2/ Fi O2 (AUC ± SE = 0.915 ± 0.018; 95% CI 0.881 to0.942). Conclusions: PaO2 and SaO2 correlated in the diagnosis of ARDS, with a PaO2/Fi O2 of 300 correlating to an SPO2/ Fi O2 of 311 (Sensitivity 90%, Specificity 80%). The SPO2/ Fi O2 ratio may allow for early real-time rapid identification of ARDS, while decreasing the cost, phlebotomy, blood loss, pain, skin breaks, and vascular punctures associated with serial arterial blood gas measurements.
Keywords: Coronary artery bypass graft surgery, Acute respiratory distress syndrome, Oxygenation indices, Ratio of arterial oxygen partial pressure to fractional inspired oxygen, Ratio of peripheral capillary oxygen saturation to fractional inspired oxygen, Ratio of partial pressure of alveolar oxygen to fractional inspired oxygen